TRADE LIBERALIZATION AND ENVIROMENTAL STANDARS - Jangkung Handoyo Mulyo (Agro Ekonomi, 2001)
This paper examines trade liberalization and environment nexus both on the theoretical ground and using empirical evidence. The results of the study reveal that there is lack of empirical evidence to conclude that industrial or capital flight is caused mainly by the implementation of lower environmental standards in host countries. Furthermore, it can be argued that the idea to impose uniform environmental standards is unfair, particularly for developing countries